"Na najlepše morje na svetu, na Jadran" - Kavrečič, Petra (Acta Histriae, 2010)
The Northern Adriatic became an attractive tourist destination in particular in the second half of the 19th century when the area witnessed the emergence of first modern forms of tourism, with the most prominent being seaside spa tourism and bathing tourism. Their development was largely spurred by medical discourses on new beneficial practices such as bathing in sea water, mud or brine and enjoying the beneficial effects of seaside air. Such health improving methods not only helped people to overcome many illnesses of that time, but also facilitated the promotion of seaside resorts. The article focuses on the tourism development in the Northern Adriatic in relation to Bohemia and later on Czechoslovakia, and studies the popularity of and familiarity with the Northern Adriatic area as a tourist destination. The research takes into consideration the period spanning from the initial phases of modern tourism development, when the afore-mentioned areas formed part of the same political entity (Austria-Hungary), to the mid-1930s. The end of WWI brought about the disintegration of the common Habsburg monarchy, with Bohemia uniting with Slovakia in Czechoslovakia, and the major part of the Eastern Northern Adriatic being ceded to the Kingdom of Italy. The new, post-war situation however did not break the tourist ties between the two areas. In the Dual Monarchy, the Bohemian lands were considered as one of the most economically prosperous areas, which enabled their population to invest in tourism infrastructure on the one hand and to enjoy the tourist offer on the other. The Northern Adriatic was an interesting region for Bohemian and later on Czechoslovak investors and tourists both before and after WWI. Until the war, Bohemians were among not only the most numerous visitors to seaside resorts mentioned in the article, but also the most important investors in accommodation facilities. The end of the war gave rise to a new political situation in Europe. Despite the new political map, the interest of Czechs to visit the Northern Adriatic resorts did not die out. Czech guests mostly ignored the suggestions to boycott the seaside resorts since then located in Italy and remained one of their most frequent visitors.
Keywords: Adriatic Sea; Czech Republic; Češka; Gradež; history; Istra; Istria; Jadransko morje; Kvarner; Kvarner Gulf; severni Jadran; tourism; Trst; Turizem; Zgodovina